Biogas dari POME: Pengaruh Lingkungan Terhadap Produksi Energi Terbarukan di Industri Kelapa Sawit - Amraini, Said Zul; Aidil, Muhammad; Senda, Semuel Pati; Haref, Yoneco; Herman, Syamsu (Department of Chemical Engineering, Faculty of Engineering, UNRI, 2024)
Palm oil mill effluent is a type of organic agro-industrial waste from the by-product of the processing of fresh oil palm fruit bunches to produce Crude Palm Oil. The management of POME as biogas is an added value for companies to meet the needs of energy sources in the Palm Oil Mill, both for Crude Palm Oil, Kernel Crushing Plant, and domestic needs as a source of electrical energy. POME is a colloidal suspension containing 95-96% water, 0.6-0.7% oil and 4-5% fat and total solids. Anaerobic degradation of POME is the main stage in the biogas production process at the Sei Pagar Palm Oil Factory. The ambient temperature was measured at 08.00, 13.00, and 18.00 for 11 days of testing. To analyze the effect of ambient temperature on sample temperature, a sample temperature test was carried out using a pH meter for each ambient temperature test. To analyze the impact of ambient temperature on the flow rate of gas produced and methane content in biogas, the sensor flow rate was checked with the valve at the reactor outlet fully open. The ambient temperature of the reactor does not change the sample temperature because the temperature in the reactor is controlled by the feed entering the reactor. The average temperature of the reactor environment is lower than the reactor so that it does not affect the gas flow rate (biogas formation process). The average temperature of the reactor environment is lower than the reactor temperature so that it does not affect the formation of methane.